1995
DOI: 10.1016/s0008-6363(95)00065-8
|View full text |Cite
|
Sign up to set email alerts
|

The electrophysiology of rabbit hearts with left ventricular hypertrophy under normal and ischaemic conditions

Abstract: There was enhanced shortening of APD and ventricular refractoriness in hypertrophied muscle during global ischaemia. This could increase the dispersion of repolarization and refractoriness between normal and ischaemic hypertrophied muscle during regional ischaemia which may explain the increased susceptibility of hypertrophied hearts to arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 44 In the present study, ischaemic ERP shortening in HCM always occurred concomitantly with enhanced APD shortening (see Supplementary material online , Figure S10 ). Indeed, both enhanced ischaemic ERP 45 , 46 and APD 21 , 45–47 shortening, and APD dispersion, 48 have been reported in various hypertrophied animal models. Interestingly, one study instead reported enhanced ischaemic ERP prolongation in hypertrophied rats.…”
Section: Discussionmentioning
confidence: 98%
“… 44 In the present study, ischaemic ERP shortening in HCM always occurred concomitantly with enhanced APD shortening (see Supplementary material online , Figure S10 ). Indeed, both enhanced ischaemic ERP 45 , 46 and APD 21 , 45–47 shortening, and APD dispersion, 48 have been reported in various hypertrophied animal models. Interestingly, one study instead reported enhanced ischaemic ERP prolongation in hypertrophied rats.…”
Section: Discussionmentioning
confidence: 98%
“…The results related to the depolarization phase of AP are not consistent. On one hand, no differences in resting membrane potential, the action potential upstroke velocity, or amplitude are documented [47,48]; on the other hand, significant changes are reported [39,49,50]. Also, there is not a consistent pattern in conduction velocity changes of hypertrophied cardiomyocytes [51,52].…”
Section: Left Ventricular Hypertrophymentioning
confidence: 97%
“…After 30 minutes of ischemia, ERP is approximately 40% longer than APD 90 . 7 Therefore, the fact that the slope of the APD restitution curve becomes flatter after development of ischemia does not necessarily mean the ERP restitution curve, which is more closely related to conduction block, undergoes the same change in slope.…”
Section: Editorial Commentmentioning
confidence: 99%